PERAWATAN PAYUDARA UNTUK MENCEGAH BENDUNGAN ASI PADA IBU POST PARTUM - Ria Gustirini (Midwifery Care Journal, 2021)
The postnatal period is the period after delivery where the mother can give baby. Breastmilk provided exclusively can meet energy and nutritional neecan grow and develop optimally. One of the causes of not achieving exclusiis that the baby does not get enough milk due to problems in breastfeedimother experiencing engorgement. If this situation continues, it can leadbreast abscess. One of the efforts to prevent breast milk damages is by breastcare aims to improve blood circulation and prevent blockage of the milk productioso as to facilitate milk production. This study aims to analyze the relationshcare in preventing breastfeeding in post partum mothers. This research analytic study with a cross sectional research design. Sampling was donesampling. Data analysis carried out included univariate and bivariatstatistical test used is the Chi-Square Test. The results showed that there wbetween breast care and the incidence of engorgement in post partum value of 0.02 (p 0.05) and an OR value of 8.7 where mothers who did nocare had a risk of 8.75 times greater. Midwives can play a role in preventingengorgement by providing counseling and teaching the steps to carry out the mother understands, understands and is able to carry out care indepen